Human capital: an analysis across the Orang Asli groups in peninsular Malaysia - Sara Shakilla Mohd Salim,; Zainal Abidin Hj Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Orang Asli or indigenous peoples are peoples with unique languages, knowledge systems and beliefs; can be separated into three main groups; Senoi, Proto-Malay and Negrito. In this article focusing on discussion about human capital among Orang Asli (aborigines) from that three main groups. This article focusing on the level of human capital ownership, physical skills, experience and participation in workshops/courses and formal education, social skills, as well as values, beliefs, and attitude towards changes and development. Human capital in the Orang Asli communities known as familiar studies in their development. Human capital that focuses more on formal education should also be expanded in the aspect of informal education, especially in the knowledge and skills of the traditional Orang Asli community as balancing of community development in their context. The importance of the study is to give general picture about their strength which comprises of knowledge and skills that they possess. Community development planning to uplift the human capital can be done based on human capital ownership (strength) of the respective ethnicity. The quality of Orang Asli’s life can be indirectly improved with the uplifting of the human capital. This study using a cross sectional survey that provides explanations on the level of human capital ownership in the Orang Asli communities. Data for this research is collected by distributing questionnaires. This study involves all head of family of Orang Asli in six villages in Pahang, and three villages in Kelantan. A total of 319 respondents involved in this study. Data collection was done by according to area and district. In general, this study shows that the level of human capital for all three groups are moderate, based on the minimum value which leads by Negrito, followed by Senoi and Proto-Malay. This proves that the level of human capital among Orang Asli needs improvisation which directly needs efforts for awareness. Orang Asli community need to be exposure in the form of development (planning,implementation, and evaluation) that can create a community to achieve community development. Due to that, Orang Asli with high human capital ownership can encourage towards capacity building and strength in community members and contribute to nation development as well.